Challenges in Diagnosis and Treatment of Lung Cancer in People with Intellectual Disabilities: Current State of Knowledge. (26th September 2016) - Satgé, Daniel; Kempf, Emmanuelle; Dubois, Jean-Bernard; Nishi, Motoi; Trédaniel, Jean
Abstract : As the life expectancy of people with intellectual disability (ID) has progressed, they have become similarly at risk of cancer as individuals of the general population. Epidemiological studies indicate a reduced incidence and mortality from lung cancer in the total population of persons with ID. However, the pattern is heterogeneous and the risk is strongly correlated with the impairment level; persons with mild intellectual impairment have higher cancer risk, and this subgroup also has the highest tobacco consumption (the major risk factor for lung cancer) compared to individuals with more severe impairment. Clinical presentation of lung cancer in persons with ID is often atypical, with symptoms frequently hidden by the mental state and communication impairments. Treatment can be impeded by incomplete understanding and lack of cooperation on the part of the patient; nevertheless, general principles for treating lung cancer must be applied to persons with ID. Early diagnosis and implementation of an adapted treatment plan may result in lung cancer outcomes similar to those of individuals in the general population. Physicians facing the difficult task of treating lung cancer in persons with ID are called to carry out their mission of care in a responsible, free, and creative way.